PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN, LITERASI PAJAK, SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Pratiwi, Endang Tri (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2024)
ABSTRACT This study aims to analyze the effect of modernization of the tax administration system, tax literacy, and tax sanctions on taxpayer compliance at the North Makassar Pratama Tax Service Office (KPP). Tax compliance data at the North Makassar Pratama Tax Service Office shows an increase each year, but the number of taxpayers reporting Annual Tax Returns does not match the number of registered taxpayers. This study uses a quantitative method with a survey method through the distribution of questionnaires to individual taxpayers. The population in this study were taxpayers registered at the North Makassar Pratama Tax Service Office. The data obtained were analyzed using regression. The results of the study indicate that modernization of the tax administration system, tax literacy and tax sanctions have a positive and significant effect on individual taxpayer compliance.